Using 2,4-D Choline Herbicide Products on 2,4-D-Tolerant Crops - Pratap Devkota; Ethan Carter; Hardeep Singh (EDIS)
This publication provides specific information on herbicide options and application requirements on newer 2,4-D formulations. The publication also provides information on the safer use of newer low-volatility formulations of 2,4-D herbicide products on Enlist crops. Written by Pratap Devkota, Ethan Carter, and Hardeep Singh, and published by the UF/IFAS Agronomy Department, July 2022.